Strategi Guru Sejarah kebudayaan Islam Dalam Mengatasi Kejenuhan Belajar Di MTs. Ulumul Qur’an - Daulay, Hardianti (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Discussion related to teacher strategies in overcoming saturation of learning islamic cultural history at MTs. This Ulumul Qur'an aims to: 1) Determine the factors that cause student learning saturation in MTs. Ulumul Qur'an; 2) Knowing the strategies used by the teacher in overcoming the boredom of learning Islamic Cultural History of students in MTs. Ulumul Qur'an. The methods used in collecting data are observation, interviews, and documentation. The results of this study, including: 1) Factors causing learning saturation experienced by students in MTs. Ulumul Qur'an is the lack of variety and motivation given by the teacher and the lack of manuals and teaching aids owned by MTs. Ulumul Qur'an so that students feel bored and bored; 2) Strategies carried out by MTs teachers. Ulumul Qur'an in overcoming the boredom of studying Islamic Cultural History of students at MTs. Ulumul Qur'an is holding various variations in teaching such as spiritual guidance, joking and telling stories.